2018
DOI: 10.1007/s11605-017-3607-7
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Assessment of Accurate Lymph Node Staging and Preoperative Detection in Resected Pancreatic Cancer

Abstract: Although the LN scoring in the seventh PDAC AJCC Staging System was sufficient to predict OS of our patients, more LNs than previously considered (20 vs. 15) were optimal to detect pathologic involvement. Preoperative LN detection was an accurate predictor of pN1 disease for treatment naïve patients without biliary obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…In a previous study using the Surveillance, Epidemiology, and End Results (SEER) database, the median number of examined LNs in patients with resected pancreatic cancer was 7 (range, 0-90), and at least 12 resected lymph nodes were required to adequately evaluate LN metastasis [14]. It is also known that the number of examined LNs in pancreatic cancer can be different according to the type of surgery [4, 6]. In this study, the number of dissected LNs was more than 12 regardless of the surgery type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study using the Surveillance, Epidemiology, and End Results (SEER) database, the median number of examined LNs in patients with resected pancreatic cancer was 7 (range, 0-90), and at least 12 resected lymph nodes were required to adequately evaluate LN metastasis [14]. It is also known that the number of examined LNs in pancreatic cancer can be different according to the type of surgery [4, 6]. In this study, the number of dissected LNs was more than 12 regardless of the surgery type.…”
Section: Discussionmentioning
confidence: 99%
“…In the AJCC 7th edition, the staging system defined all regional LN metastases as N1. The 8th edition was revised to further evaluate the LN grade based on the number of metastatic nodes [4].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of LN metastasis in pancreatic cancer is accomplished by the tumor node metastasis (TNM) staging system. The seventh edition of the American Joint Committee on Cancer (AJCC) classification system defined N1 as the presence of any number of positive regional LNs, whereas in the eighth edition of AJCC nodal classification was further categorized on the number of positive nodes [6].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Fifteen resected LNs are considered oncologically enough, but it has been suggested that 20 was the optimal number, especially in chemotherapy-naive patients. 21 In our specimens, a median of 26 LNs were retrieved, which alludes to the extent of peripancreatic lymphoid tissue clearance and compares favorably to the number of examined LNs reported by most established pancreatic centers. 22…”
Section: Discussionmentioning
confidence: 61%